Systematic Literature Review: Research on Pencak Silat using Vos Viewers in the Scopus Database for 2018-2022 - Wardoyo, Hendro; Setiakarnawijaya, Yasep (UNIB Press, 2023)
Pencak silat is a branch of full body contact martial arts which is categorized as a strenuous sport where the body requires quite a lot of energy to produce excellent physical condition in supporting techniques and tactics. This study uses a descriptive quantitative method with a bibliometrics approach. The research data used for scientific journals or articles spanning 2018-2022 is sourced from the Scopus database. A scientific article search was carried out using the Publish or Perish application with the keyword